The Architect of Himself: Forging Essence through Existential Choices in Pashupati Prasad - Pradhan, Nani Maiya (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2025)
Constructing the self in the realm of human society begets multiple challenges as the uncertainty of human life struggles in the immensity of human problems. However, human beings are compelled to exist because they are condemned to live; they are self-denying creatures who validate and make their life meaningful themselves. In this regard, this paper explores the process of constructing essence through existential choices in Pashupati Prasad (2016), a film directed by Dipendra K. Khanal, in light of the existentialist perspective. As the film depicts the struggle of Pashupati Prasad, the protagonist, it shows the existential choices that give meaning to his life. The relentless struggle makes him an existentialist who dares to challenge the constraints rather than surrender. In this connection, this research paper deals with three specific questions: Why does the film portray human difficulty as the driving force to make existential decisions? How does the film expose the existential choice of the protagonist that ignites his process of cultivating himself and illuminating his essence? What allows Pashupati Prasad to make his decision subjective, autonomous, and existential? To answer these questions, this research employs Jean-Paul Sartre's notion of 'existence precedes essence' and claims that the film Pashupati Prasad exposes human continuous refurbishment in the perpetuation of the process of becoming. It reveals that human beings are involved in the signifying process of essence through existential choices, which is entirely a subjective process, but the process is entrapped in a vicious cycle that never ends